Genomic innovation of ATD alleviates mistranslation associated with multicellularity in Animalia - Kuncha, Santosh Kumar; Venkadasamy, Vinitha Lakshmi; Amudhan, Gurumoorthy; Dahate, Priyanka; Kola, Sankara Rao; Pottabathini, Sambhavi; Kruparani, Shobha P; Shekar, P Chandra; Sankaranarayanan, Rajan (eLife, 2020)
The emergence of multicellularity in Animalia is associated with increase in ROS and expansion of tRNA-isodecoders. tRNA expansion leads to misselection resulting in a critical error of L-Ala mischarged onto tRNAThr, which is proofread by Animalia-specific-tRNA Deacylase (ATD) in vitro. Here we show that in addition to ATD, threonyl-tRNA synthetase (ThrRS) can clear the error in cellular scenario. This two-tier functional redundancy for translation quality control breaks down during oxidative stress, wherein ThrRS is rendered inactive. Therefore, ATD knockout cells display pronounced sensitivity through increased mistranslation of threonine codons leading to cell death. Strikingly, we identify the emergence of ATD along with the error inducing tRNA species starting from Choanoflagellates thus uncovering an important genomic innovation required for multicellularity that occurred in unicellular ancestors of animals. The study further provides a plausible regulatory mechanism wherein the cellular fate of tRNAs can be switched from protein biosynthesis to non-canonical functions.
Keywords: tRNA Isodecoder; proteostasis; translation; proofreading; multicellularity; Aminoacyl-tRNA Synthetase